HUBUNGAN SOSIAL BUDAYA, PERSEPSI EFEK SAMPING DAN GANGGUAN HUBUNGAN SEKSUAL DENGAN PEMILIHAN IUD DI KECAMATAN BANYUBIRU KABUPATEN SEMARANG TAHUN 2018 - Duhita Wikalaili Enzimatia; Dharminto Dharminto; R. Djoko Nugroho; Sri Winarni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
IUD is one of the contraceptive methods that sugested by BKKBN and PB-POGI with 98% program effectiveness but IUD users in Indonesia are still relatively low (5%). Banyubiru sub-district has the lowest MKJP user in Semarang Regency with 4.77% IUD user in 2018. This study aims to analyze socio-cultural relations, perception of side effects and sexual disfunction with election of IUD. This research uses explanatory research methods and case control study design. The population of this research is 64 IUD user and 1237 non-IUD users. Tthe sample used is 33 IUD users and 66 non-IUD controls (simple random sampling). The result of univariate analysis showed that didn’t hamper social culture (58,6%), proper perseption of side effects (53,5%), minor perception of sexual disfunction (59,6%). Chi-Square analysis result with α of 0,05, election of IUD have relation with perception of side effects (p-value =0,001;OR=12,688) and perception of sexual disfunction p-value=0,001;OR=46,222), socio-cultural haven’t relation with election of IUD (p-value= 0,614;OR=0,729). Logistic regression analysis shows that independent variable to have influence on proper side effects of 5 times and perception of minor sexual disfunction of 23 times, social culture haven’t influence with election of IUD. Suggestions are given by giving IEC and interpersonal communication to the IUD acceptor about side effect and sexual disorders with IUD.Keywords : election of IUD, social culture, perception of side effects, perception of sexual disfunction